Improving diagnostic yield in obscure gastrointestinal bleeding - how virtual chromoendoscopy may be the answer - Castro, Francisca Dias de (2015)
Background and aim: A significant proportion of patients presenting with obscure gastrointestinal bleeding (OGIB) have negative small bowel capsule endoscopy (SBCE) examinations, and yet remain at risk of rebleeding. We aimed to evaluate whether a second-look review of SBCE images using flexible spectral color enhancement (FICE) may improve the detection of potentially bleeding lesions. Materials and methods: This was a retrospective, single-center study including consecutive patients with OGIB subjected to SBCE, whose standard white light examination was nondiagnostic. Each SBCE was reviewed using FICE 1. New findings were labeled as either P1 or P2 lesions according to bleeding potential. Patients were followed up to assess the incidence of rebleeding. Results: A total of 42 consecutive patients were included. Sixteen patients (38%) experienced rebleeding after a mean follow-up of 26 months. Review of SBCE images using FICE 1 enabled the identification of previously unrecognized P2 lesions, mainly angioectasias, in nine patients (21%) and P1 lesions, mainly erosions, in 26 patients (62%). Among patients who experienced rebleeding, 13/16 (81%) were diagnosed with P1 lesions with FICE 1 (P=0.043), whereas 3/16 (19%) had confirmed nondiagnostic SBCE and only 1/16 (6%) had newly diagnosed P2 (plus P1) lesions. An alternative source of bleeding outside the small bowel was found in only 3/16 (19%) patients with rebleeding during the follow-up. Conclusion: In a significant proportion of patients with OGIB, FICE 1 may detect potentially bleeding lesions previously missed under conventional white light SBCE. Review of nondiagnostic SBCE with FICE 1 may be a valuable strategy to obviate the need for further investigations in patients with OGIB, particularly for those who experience rebleeding.